P449 Minimally invasive IPAA in UC: Preliminary results from a referral center. (30th January 2023) - Fortuna, L; Bottari, A; Ficari, F; Cricchio, M; Cianchi, F; Scaringi, S
Abstract: Background: Minimally invasive approaches in performing restaurative total proctocolectomy in Ulcerative Colitis(UC) have been increasingly adopted. In particular, the robotic approach could be used with more benefits in proctectomy with ileal pouch anal anastomosis (IPAA). In fact, the robotic device seems to potentially overcome all the limitations found in laparoscopic and conventional open surgery. The aim of our study was to compare and evaluate early and late functional postoperative outcomes and complications after IPAA, performed with open, laparoscopic and robotic techniques in UC patients. Methods: At our institution, 397 UC patients who underwent restorative proctocolectomy with IPAA during the period 1986-2022, consecutively treated either with open surgery, laparoscopic or robotic techniques were enrolled. The incidence of early (<30 days) and late (>30 days) postoperative complications (intestinal occlusion, haematoma/wound infection, anastomotic dehiscence), hospital stay and an assessment about continence, autonomic nerve damage, incidence of pouchitis and cuffitis was evaluated. Results: About the 397 patients, 344 underwent conventional open IPAA, 31 laparoscopically and 22 robotically. Comparable early and late postoperative surgical complications were recorded among the different techniques [early and late complications respectively 24/53 (45, 2%) and 146/344(42, 4%)] in minimally invasive and open groups. Minimally invasive surgery showed a better outcome regarding wound infections [0/53 (0%)], anastomotic dehiscence and reduced length of stay but open surgery demonstrated a better result on early and late intestinal occlusion [8/53 (15%)vs 22/344 (6, 39%)] and anastomotic stenosis [5/53 (9, 43%) vs 15/344 (4, 36%)]. Lastly, the rate of cuffitis was higher in open surgery than in the minimally invasive group [(3/53 (5, 66%) vs 46/344(13, 37%)] and within these, robotic approach seems to show better results compared to laparoscopy. Conclusion: UC patients undergoing IPAA could benefit from a minimally invasive surgical approach. Our experience confirms that robotics seems to be related to hopeful outcomes both in the short and long term period, even if more studies are needed to refine the promising results.